2016
DOI: 10.2147/copd.s94709
|View full text |Cite
|
Sign up to set email alerts
|

Effect of salmeterol/fluticasone combination on the dynamic changes of lung mechanics in mechanically ventilated COPD patients: a prospective pilot study

Abstract: BackgroundThe combined therapy of inhaled corticosteroids and long-acting beta-2 agonists for mechanically ventilated patients with COPD has never been explored. Therefore, the aim of this study was to investigate their dynamic effects on lung mechanics and gas exchange.Materials and methodsTen mechanically ventilated patients with resolution of the causes of acute exacerbations of COPD were included. Four puffs of salmeterol 25 μg/fluticasone 125 μg combination therapy were administered. Lung mechanics, inclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 36 publications
1
6
0
Order By: Relevance
“…However, the decreased values gradually returned to the baseline values after the 6 h time point. This finding is the same as that in our previous study evaluating the effects of salmeterol and fluticasone on lung mechanics in patients receiving mechanical ventilation, which revealed that salmeterol has the maximum bronchodilation effect, causing 15% lower PIP than the baseline value [ 23 ]. Malliotakis et al evaluated the duration of salmeterol-induced bronchodilation and noted that salmeterol led to an approximately 10% reduction in PIP at 2 to 6 h but that the PIP gradually returned to the baseline after the 6 h time point [ 7 , 30 ].…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…However, the decreased values gradually returned to the baseline values after the 6 h time point. This finding is the same as that in our previous study evaluating the effects of salmeterol and fluticasone on lung mechanics in patients receiving mechanical ventilation, which revealed that salmeterol has the maximum bronchodilation effect, causing 15% lower PIP than the baseline value [ 23 ]. Malliotakis et al evaluated the duration of salmeterol-induced bronchodilation and noted that salmeterol led to an approximately 10% reduction in PIP at 2 to 6 h but that the PIP gradually returned to the baseline after the 6 h time point [ 7 , 30 ].…”
Section: Discussionsupporting
confidence: 89%
“…Malliotakis et al evaluated the duration of salmeterol-induced bronchodilation and noted that salmeterol led to an approximately 10% reduction in PIP at 2 to 6 h but that the PIP gradually returned to the baseline after the 6 h time point [ 7 , 30 ]. Other major parameters evaluated in the current study—such as Pmean, Pplat, and Rrs—reached their minimum at 6 h after tiotropium SMI actuation but had returned to the baseline value by 12 h. The greatest change was observed in Rrs, which was decreased by approximately 13% at 6 h. The poor performance of long-acting bronchodilators in mechanically ventilated patients compared with that in spontaneously breathing patients may be due to multiple factors such as use of a chamber with MDIs, connection of the inhalation device to the inspiratory line at 10–30 cm from the endotracheal tube, humidity in the ventilator circuit, the tidal volume setting, the inspiration flow rate, the respiratory frequency, and use of a breath-holding maneuver after inhalation [ 5 , 23 , 29 ]. Although several studies have measured lung mechanics after administering long-acting bronchodilators [ 5 , 16 , 17 , 23 , 30 , 31 ], our findings imply that the dose to the patients with COPD receiving mechanical ventilation was insufficient due to the limitations of the mechanical ventilated circuit and setting.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Rrs and Crs values used for the four respiratory mechanics profiles (obstructive, mildly restrictive, severely restrictive and mixed obstructive/restrictive) in this study were based on previously published data. For example, Salihoglu et al reported dynamic respiratory compliance (Cdyn) and airway resistance (Raw) of 40±8 mL/cmH 2 O and 19±4 cmH 2 O/L/s, respectively, in intubated patients with COPD in the supine position [36]. In 10 mechanically ventilated patients with acute exacerbations of COPD, Chen et al determined Raw and Crs to be 17.4±7.6 cmH 2 O/L/s and 46.0±23.6 mL/cmH 2 O, respectively [37].…”
Section: Discussionmentioning
confidence: 99%
“…In patients receiving long-term ventilation for severe COPD, Nava and Compagnoni observed a small but statistically significant reduction in airway resistance with fluticasone. 169 A combination of salmeterol and fluticasone administered to mechanically ventilated patients by pMDI (4 doses) reportedly reduced inspiratory resistance, 170 but this effect was probably because of the salmeterol component in the combination. Despite the lack of studies showing efficacy of ICS in the setting of mechanical ventilation, the majority of respondents reported employing inhaled budesonide or methylprednisolone in international surveys.…”
Section: Avoid Inappropriate Therapiesmentioning
confidence: 99%